The distribution of national income in Germany, 1992-2019 - Stefan Bach; Charlotte Bartels; Theresa Neef (Halle Institute for Economic Research (IWH), 2024)
This paper analyzes the distribution and composition of pre-tax national income in Germany since 1992, combining personal income tax returns, household survey data, and national accounts. Inequality rose from the 1990s to the late 2000s due to falling labor incomes among the bottom 50% and rising incomes in the top 10%. This trend reversed after 2007 as labor incomes across the bottom 90% increased. The top 1% income share, dominated by business income, remained relatively stable between 1992 and 2019. A large share of Germany's top 1% earners are non-corporate business owners in labor-intensive professions. At least half of the business owners in P99-99.9 and a quarter in the top 0.1% operate firms in professional services - a pattern mirroring the United States. From 1992 to 2019, Germany's top 0.1% income concentration exceeded France's and matched U.S. levels until the late 2000s.
Keywords: D31; E01; H2; H5; J3; 330; capital income; income distribution; labor income; top incomes